Governance of Online Electronic Patient Medical Records Distribution - Alzeta Rosdyana; Kamila Najmil Khaira; Yuda Syahidin; Yuyun Yunengsih (LPPM Universitas Islam 45 Bekasi, 2023)
The distribution of medical records at Kebonjati Hospital, especially for patients who register online, still uses a manual system which can obstruct the data search process, therefore a computerized system is needed. This study aims to design an information system for distributing outpatient medical records for online patients. The research method is descriptive qualitative, data collected through interviews and case studies. The system development method uses the Agile Software Development method with the stages of planning, implementation, testing, documentation, deploying, and maintenance then implemented using Microsoft Visual Studio 2012 into the Visual Basic programming language. The research designed an information system for distributing outpatient medical records online at Kebonjati Hospital that had been adapted to the needs of medical recorders. This information system is in the form of applying the concept of clinical management by designing good services and developing quality work plans for hospital management purposes.